Indole Compounds in Oncology: Therapeutic Potential and Mechanistic Insights - Sara M. Hassan; Alyaa Farid; Siva S. Panda; Mohamed S. Bekheit; Holden Dinkins; Walid Fayad; Adel S. Girgis (MDPI AG, 2024)
Cancer remains a formidable global health challenge, with current treatment modalities such as chemotherapy, radiotherapy, surgery, and targeted therapy often hindered by low efficacy and adverse side effects. The indole scaffold, a prominent heterocyclic structure, has emerged as a promising candidate in the fight against cancer. This review consolidates recent advancements in developing natural and synthetic indolyl analogs, highlighting their antiproliferative activities against various cancer types over the past five years. These analogs are categorized based on their efficacy against common cancer types, supported by biochemical assays demonstrating their antiproliferative properties. In this review, emphasis is placed on elucidating the mechanisms of action of these compounds. Given the limitations of conventional cancer therapies, developing targeted therapeutics with enhanced selectivity and reduced side effects remains a critical focus in oncological research.